Reassembling sex: reconsidering sex segregation policies in sport. Issue 2 (3rd April 2018) - Kerr, Roslyn; Obel, C.
ABSTRACT: Over the last decade, cases such as Caster Semenya's have drawn attention to the problematic nature of sex segregation policies in elite sporting competition. Several authors have emphasised that sex segregation policies are based on questionable evidence and do not facilitate fair competitions. This article uses the concept of the assemblage, as derived from Bruno Latour's work in Actor-Network Theory, to highlight how, through considering the body as made up of multiple traits, it is possible to arrive at a classification system that is fairer than the current two-sex binary, and more logically based on the different physical traits required in various sports. Using the example of the change from a medical classification system to a functional system in disability sport, we outline and discuss a model for able-bodied sport as an alternative to the current sex segregation, which involves classifying bodies based on functional ability across multiple traits.